Pengaruh E-Promotion Official Instagram, Rating Google Maps, dan Metode Pembayaran terhadap Keputusan Pembelian Iphone di IBGADGETSTORE Purwokerto - Ricky Annas Saputra; Yugi Setyarko (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the influence of E-Promotion through Instagram, Google Maps Rating, and payment methods on iPhone purchasing decisions at Ibgadgetstore Purwokerto. The background of this study is based on the importance of digital marketing strategies and the ease of payment systems in influencing consumer behavior in the modern era. Along with the development of technology, consumers increasingly rely on social media and digital platforms to search for information before making a purchase. Therefore, companies are required to be able to utilize digital promotional media optimally, provide flexible payment systems, and maintain reputations through online reviews. The research method used is a quantitative approach with a survey technique. Data were collected by distributing questionnaires to consumers who have made transactions at Ibgadgetstore. The number of samples was set at 111 respondents using a non-probability sampling technique. The collected data were then analyzed using multiple linear regression methods using SPSS software, so that an overview of the influence of each independent variable on purchasing decisions was obtained. The results showed that the three independent variables, namely E-Promotion, Google Maps Rating, and payment methods, had a positive and significant effect both partially and simultaneously. E-Promotion through Instagram was proven to increase consumer purchasing interest by presenting interactive, interesting, and informative promotional content. Google Maps ratings strengthen consumer trust in stores through positive reviews and transparent digital ratings. Meanwhile, diverse, secure, and flexible payment methods can encourage consumers to make faster purchasing decisions because they perceive the transaction process as easier. Thus, this study confirms that digital marketing strategies, online reputation, and payment convenience play a significant role in influencing consumer purchasing decisions.